Fluorescent Dyes with Large Stokes Shifts Based on Benzo[1, 2‐d:4, 5‐d']bis([1, 3]dithiole) ("S4‐DBD Dyes"). Issue 11 (10th March 2020) - Wessig, Pablo; Freyse, Daniel; Schuster, David; Kelling, Alexandra
Abstract : We report on a further development of [1, 3]‐dioxolo[4.5‐ f ]benzodioxole (DBD) fluorescent dyes by replacement of the four oxygen atoms of the heterocyclic core by sulfur atoms. This variation causes striking changes of the photophysical properties. Whereas absorption and emission significantly shifted to longer wavelength, the fluorescence lifetimes and quantum yields are diminished compared to DBD dyes. The latter effect is presumably caused by an enhanced intersystem crossing to the triplet state due to the sulfur atoms. The very large Stokes shifts of the S 4 ‐DBD dyes ranging from 3000 cm –1 to 7400 cm –1 (67 nm to 191 nm) should be especially emphasized. By analogy with DBD dyes a broad variation of absorption and emission wavelength is possible by introducing different electron withdrawing substituents. Moreover, some derivatives for coupling with biomolecules were developed. Abstract : Replacing oxygen by sulfur atoms substantially changes the photophysical behavior of DBD dyes. While fluorescence quantum yields and lifetimes are decreased, absorption and emission wavelength markedly red‐shifted. The very large Stokes shifts should be especially emphasized. A series of S 4 ‐DBD dyes with different electron withdrawing groups were prepared enabling a broad range of emission wavelength.